2019
DOI: 10.14744/tjtes.2019.38969
|View full text |Cite
|
Sign up to set email alerts
|

The thiol-disulphide homeostasis in patients with acute pancreatitis and its relation with other blood parameters

Abstract: BACKGROUND: Acute pancreatitis is a common disease seen in emergency departments because of abdominal pain. The present study aims to evaluate the relation between measurements of thiol-disulfide parameters in patients diagnosed with acute pancreatitis and other blood parameters. METHODS: A total of 56 (56%) patients, who were admitted to the emergency department, and 44 (44%) healthy volunteers participated in this study. A total of 100 samples were taken from the participants. Detailed blood samples were tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This study demonstrated that sh levels were significantly lower in AP patients than in healthy volunteers. Studies on thiol/disulfide parameters in AP patients have shown similar results to our study (1,6,8). However, Özyazıcı et al studied thiol/disulfide parameters among AP patients and showed that sh levels were significantly lower in AP patients than in control group patients (13).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study demonstrated that sh levels were significantly lower in AP patients than in healthy volunteers. Studies on thiol/disulfide parameters in AP patients have shown similar results to our study (1,6,8). However, Özyazıcı et al studied thiol/disulfide parameters among AP patients and showed that sh levels were significantly lower in AP patients than in control group patients (13).…”
Section: Discussionsupporting
confidence: 86%
“…Oxidative stress may trigger many pathologic mechanisms, such as lipid peroxidation, enzymatic activation/deactivation, DNA damage, and immune system deficiency (5). Thiol, an organic component that contains sulfhydryl group (-SH), plays a vital role in antioxidative mechanisms (6). The thiol groups are oxidized by oxygen radicals and turn into reversible disulfide bond structures.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters were investigated in the diagnosis of many causes of acute abdomen. [7][8][9] In addition to inflammatory markers, oxidative stress markers have recently become focus of interest in research efforts. In the literature, there is limited number of experimental and clinical trials addressing relationship between acute abdomen and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%